THE WORLD IN 2030 AS SEEN BY EXPERTS OF THE US NATIONAL INTELLIGENCE COUNCIL - A. I. Nikitin; E. S. Voronin; F. K. Zvedre; V. N. Zemskov; M. A. Nebolsina; A. P. Grzha; O. L. Son; D. N. Novikova (Vestnik MGIMO-Universiteta, 2013)
.